Evaluation of the Reference Tissue Models for PET and SPECT Benzodiazepine Binding Parameters - Millet, Philippe; Graf, Christophe; Buck, Alfred; Walder, Bernard; Ibáñez, Vicente (NeuroImage (Orlando, Fla.), 2002)
Recently, reference tissue methods have been proposed to estimate binding potential from PET data. A reference region without specifically bound ligand is used as an indirect input function to enable the expression of the time–concentration curve of a region of interest using a compartment model. However, PET dopaminergic and serotoninergic studies have shown differences between binding potential (BP) values obtained with reference tissue methods and those obtained with conventional kinetic modeling using an arterial input function. In this study, we measured the BP values for the benzodiazepine receptors in seven subjects using PET [ 11C]flumazenil and SPECT [ 123I]iomazenil radioligands. We compared the BP values obtained using the reference tissue methods with those obtained using the conventional kinetic method. These values were also compared with the absolute value of receptor density, B max ′. For the PET studies, a multi-injection approach employing labeled and unlabeled flumazenil was used to estimate the main binding parameters, BP and B max ′. For SPECT studies, a single injection protocol of [ 123I]iomazenil was used to estimate BP values. The BP values were estimated using one- and two-tissue compartment models for the target region. Similar BP values were obtained using either the one- or two-tissue compartment model. This is probably due to the rapid equilibrium between tissue compartments reached with these radioligands. For PET and SPECT, these BP values were highly correlated ( r > 0.960) to the BP values obtained using the arterial input function. We also found high correlations between the BP values obtained using the simplified reference tissue method and the receptor density parameter B max ′ ( r > 0.884). However, the reference tissue methods yielded lower BP values than those obtained using the conventional approach. Moreover, there was a bias on BP values that was not a simple scaling. It seems that the physiological values found in gray matter structures using these radioligands give acceptable BP values. We conclude that the reference tissue methods should be carefully evaluated for each radioligand.